2004
DOI: 10.1103/physreva.70.023606
|View full text |Cite
|
Sign up to set email alerts
|

Three-level atom optics via the tunneling interaction

Abstract: Three-level atom optics is introduced as a simple, efficient, and robust method to coherently manipulate and transport neutral atoms. The tunneling interaction among three trapped states allows us to realize the spatial analog of the stimulated Raman adiabatic passage, coherent population trapping, and electromagnetically induced transparency techniques and offers a wide range of possible applications. We investigate an implementation in optical microtrap arrays and show that under realistic parameters the coh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
189
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(190 citation statements)
references
References 23 publications
1
189
0
Order By: Relevance
“…Recently, it has been shown that similar techniques can, in principle, be used to control the quantized center-of-mass state of single particles [4][5][6]. This atom-optical analog has been dubbed coherent transport by adiabatic passage (CTAP) and while the possibility of observing this process has received significant attention [7,8], the conditions that have to be fulfilled for its observation are currently hard to achieve experimentally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that similar techniques can, in principle, be used to control the quantized center-of-mass state of single particles [4][5][6]. This atom-optical analog has been dubbed coherent transport by adiabatic passage (CTAP) and while the possibility of observing this process has received significant attention [7,8], the conditions that have to be fulfilled for its observation are currently hard to achieve experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the strength of the tunnel coupling is usually adjusted by changing the distance between the microtraps, which leads to significant overlap of the neighboring trapping potentials, the eigenstates become time dependent. Several solutions to the problem have been suggested, all involving significant experimental resources or restrictions on the parameter space [4,6,7]. A similar process coupling classical light between optical waveguides has recently been experimentally demonstrated [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Our first goal will consist of developing an efficient and robust method to adiabatically transport holes between the two extreme traps of the triple-well potential, by applying the matter-wave analog [10] of the quantum optical STIRAP technique [11]. Thus, let us consider three in-line traps with one empty site and two identical fermions, each one in the vibrational ground state of the two remaining traps as shown in Fig.…”
Section: Adiabatic Transport Of Holesmentioning
confidence: 99%
“…For truncated harmonic traps, see Eq. (2), the J i tunneling rate of a single atom between the ground states of two adjacent traps i and i + 1 is given by [10] …”
Section: Adiabatic Transport Of Holesmentioning
confidence: 99%
See 1 more Smart Citation